Improving Students’ Speaking Skill Through Short Answer Questions (SAQS) - Sarifuddin, Muhamad (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
This research is aimed at finding out  whether the application of the Technological Pedagogical Content Knowledge Approach (TPACK) is effective or not in teaching students speaking skills to students at MA MA Putra Al-Islahuddiny Kediri in Academic Year 2024/2025. The research was an experimental research and the design was used as one group pre-test and post-test. The population of the study was the XI grade students of MA Putra Al-Islahuddiny Kediri in Academic Year 2024/2025. The sample of this was taken only 22 students. The data was collected through speaking test namely interview. This research had been done in eight meetings. For the data analysis, the researcher used parametric statistics, namely Paired Sample T-test through SPSS. The results of the analysis showed that the Sig. (2-tailed) is 0.000 so that because the value of Sig. (2-tailed) < 0.05 (5%) then Ho is rejected and Ha is accepted so that there is an effect of the short answer questions technique/ SAQs speaking for the XI grade students at MA Putra Al-Islahuddiny Kediri in Academic Year 2024/2025.